(untitled) (Research, Society and Development, 2021)
Objective: To characterize female and male adolescents regarding behavioral variables and use of contraceptive methods, and identify and associate the self-efficacy score in male condom use among female and male adolescents at a public school. Methodology: This is a descriptive, cross-sectional study with a quantitative approach, with 95 adolescents enrolled in the afternoon and night shifts of a public school in the interior of Minas Gerais, carried out in February 2020. Results: The male condom was the method of choice most used by both girls (27.6%) and boys (90%). The average score of respondents in relation to self-efficacy among males was 58.8 points (sd=6.4); in relation to female adolescents, they were 58.2 points (sd=8.3). In the bivariate analysis, the variables: sexual intercourse (p=0.88; p=0.13), work (p=0.80; p=0.88), physical activity (p=0.89; p=0 .08) and leisure activity (p=0.79; p=0.87) were not associated with a higher self-efficacy score in condom use among adolescents. Conclusion: It is concluded that adolescents showed good self-efficacy in relation to the use of male condoms, and showed that it is not related to some variables that could enhance the evidence.